1988
DOI: 10.1007/bf01796896
|View full text |Cite
|
Sign up to set email alerts
|

The impact of first-birth timing on divorce: New evidence from a longitudinal analysis based on the central population register of Norway

Abstract: "The association between divorce risks in first marriage and the timing of the first birth is inspected in a life-table analysis of registered birth and marriage histories from Norway. One of the main conclusions is that the high propensity to divorce among women who have had a premarital birth is not confined to those who marry someone other than the father of their child. Also, women who have had a premarital child with their husband, run a much higher risk of marital breakup than do those who had their fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…It is a common finding thai premarital births are associated with higher subsequent divorce risks. See, for example, Menken et al (1981) or Martin and Bumpass (1989) for findings from U.S. data, and Kravdal (1988) for an analysis of the impact of first-birth timing on divorce risks in Norway. The presence of premarital children may reflect a number of different premarital life histories of the mothers.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…It is a common finding thai premarital births are associated with higher subsequent divorce risks. See, for example, Menken et al (1981) or Martin and Bumpass (1989) for findings from U.S. data, and Kravdal (1988) for an analysis of the impact of first-birth timing on divorce risks in Norway. The presence of premarital children may reflect a number of different premarital life histories of the mothers.…”
Section: Methodsmentioning
confidence: 98%
“…For remarried women, one or more of the "premarital" children may, alternatively, be from a previous marriage. Kravdal (1988) has shown that for first marriages, the presence of premarital children is connected with increased divorce risks, even in marriages where the father is the current husband. We cannot distinguish between the various possible forms of paternity in our register data, for they contain no information about fathers or about periods of cohabitation, though the general picture of Swedish family patterns indicates that most premarital children are born into a cohabitational relationship that is subsequently converted into a marriage with the father.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Having a first birth within wedlock has been reported to decrease the risk of divorce in Norway and Sweden (Kravdal 1988;Liu 2002). This effect is most likely due to selection of particularly stable couples into marriage before the first birth, as in these countries, the majority of first births are now to cohabiting mothers.…”
Section: Childrenmentioning
confidence: 99%
“…They have hypothesized that 'the remaining excess risk of divorce for mothers of premarital children may stem from the fact that their husband are not these children's biological fathers' (Qvist et al 1995; for a review, see Andersson, 1997). Actually, using Norwegian registers, Kravdal (1988) has found that for women in their first marriages, the presence of premarital children indeed lead subsequently to higher risk of divorce, even the father of the premarital children is the woman's current husband.…”
Section: Introductionmentioning
confidence: 99%